2016
DOI: 10.1111/apa.13325
|View full text |Cite
|
Sign up to set email alerts
|

Low maternal education and socio‐economic status were associated with household food insecurity in children under five with diarrhoea in Bangladesh

Abstract: Aim Household food insecurity (HFI) is insufficient access to nutritionally safe and adequate foods to meet the dietary needs for an active and healthy life. We examined the prevalence and determinants of HFI in Bangladeshi children under five with diarrhoea. Methods This study included 365 children (55% boys) who had diarrhoea in the two weeks before the 2011 Bangladesh Demographic Health Survey (BDHS‐2011). The Household Food Insecurity Access Scale (HFIAS) was used to assess HFI and Pearson's chi‐square tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 17 publications
2
17
0
Order By: Relevance
“…In pregnancy, some aspects of a woman's life may play a major role during the gestational period and for neonatal outcomes, especially in adverse social contexts [10,11]; such effects were estimated to occur for approximately 70% of pregnant women in Nigeria [12] In this sense, FI can be an important variable for the presence or aggravation of stressful pregnancy events by compromising access to sufficient and quality food, as well as increasing clinical complications during pregnancy and childbirth and in newborns [8,13,14]. Some relationships of FI with pregnancy have been documented in previous studies, such as associations of FI with overweight in mothers [5], low birth weight [15], low weight in children, inadequate development, overweight, impaired cognitive development, and behavioural and emotional factors [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In pregnancy, some aspects of a woman's life may play a major role during the gestational period and for neonatal outcomes, especially in adverse social contexts [10,11]; such effects were estimated to occur for approximately 70% of pregnant women in Nigeria [12] In this sense, FI can be an important variable for the presence or aggravation of stressful pregnancy events by compromising access to sufficient and quality food, as well as increasing clinical complications during pregnancy and childbirth and in newborns [8,13,14]. Some relationships of FI with pregnancy have been documented in previous studies, such as associations of FI with overweight in mothers [5], low birth weight [15], low weight in children, inadequate development, overweight, impaired cognitive development, and behavioural and emotional factors [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, within a given region or population, the impacts of food insecurity are quite heterogeneous, often conditioned by a given family's or community's social, cultural, or economic capital. For example, in diverse settings, factors such as household size, maternal age or educational status, and status of civil or marriage unions all have a profound impact on food security [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Poorest and poorer families are less likely to have the financial resources to buy healthy or enough food. [19,20] The evidence generated from a systematic review of literature also revealed that young age of the child (usually <24 months), and low socioeconomic status are the risk factors of acute childhood diarrhea. [17]…”
Section: Discussionmentioning
confidence: 99%